Techno-economical and ecological potential of electrical scooters : A life cycle analysis - Markus Kazmaier and Tessa T. Taefi and Tim Hettesheimer (European journal of transport and infrastructure research, 2020)
In Germany, mobility is currently in a state of flux. Since June 2019, electric kick scooters (e-scooters) have been permitted on the roads, and this market is booming. This study employs a user survey to generate new data, supplemented by expert interviews to determine whether such e-scooters are a climate-friendly means of transport. The environmental impacts are quantified using a life cycle assessment. This results in a very accurate picture of e-scooters in Germany. The global warming potential of an e-scooter calculated in this study is 165 g CO2-eq./km, mostly due to material and production (that together account for 73% of the impact). By switching to e-scooters where the battery is swapped, the global warming potential can be reduced by 12%. The lowest value of 46 g CO2-eq./km is reached if all possibilities are exploited and the life span of e-scooters is increased to 15 months. Comparing these emissions with those of the replaced modal split, e-scooters are at best 8% above the modal split value of 39 g CO2-eq./km.
Keywords: E-mobility; E-scooter; First and last mile connectivity; LCA; Micromobility; Shared mobility; Urban mobility